Kære Hr. Professor! 11 breve fra Michael Neiiendam til J. Oskar Andersen 1920-22 - Licht, Christian de Fine (Kirkehistoriske Samlinger, 1994)
On three study tours to Göttingen, Berlin and Paris in 1920-22, the theologian Michael Neiiendam (1895-1962) became acquainted with a number of well known German professors of theology. In eleven letters to his Danish teacher, professor J. Oskar Andersen (1866-1959) of the Copenhagen University, he presents accurate portraits of them as well as details of the difficult economic conditions in Germany in the after war years. Michael Neiiendam worked on his thesis for the doctorate, which he recieved in 1922. His subject was the Age of Enlightenment and its influence on Danish theology. His letters suggest a natural connection between the subject of his thesis and the modern liberal theology of his own time, exemplified in his particular interest in the works of Albrecht Ritschl, Ernst Troeltsch and Carl Stange. At the end ofthe period, covered by these letters, Michael Neiiendam abandons hopes of a career, teaching at the Copenhagen University. In 1923 he marries and settles down as assistent vicar in a parish north of Copenhagen, but soon afterwards, he starts giving lectures at the university as well.